(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of the study was to evaluate knowledge, awareness, and practice related to forensic odontology among dental students in Chennai.Methods: This cross-sectional study was conducted among the dental students in Chennai . To evaluate the knowledge of the participants about forensic dentistry, a self-administered questionnaire containing 10 questions pertained was made. Results: A total of 125 participants were included in this study out of which, 75.20% were males and the remaining 24.80% were females.86.40% of the participants said that they were aware about the bite mark patterns of the teeth and the remaining 13.60% of the participants said that they were not aware about the bite mark patterns of the teeth.Conclusion: The results show that there is an adequate level of knowledge and awareness regarding forensic odontology in all the groups investigated. Overall, the three groups also had adequate levels of good practice related to dental record keeping. However, regarding individual questions, there were some instances among the groups of inadequate levels of good practice.